Influence of education on oro-dental knowledge among school hygiene instructors - Soussan Irani; Marjane Meschi; Azizollah Goodarzi (Tabriz University of Medical Sciences, 2009)
Background and aims. Recent progresses in preventive dentistry and their correct application in many developed countries have remarkably decreased the rate of oro-dental diseases in children and teenagers, while the rate of oro-dental diseases is on the rise among the children in developing countries. The aim of this study was to evaluate the impact of educating school health care instructors by measuring their level of oral health knowledge and their opinions about the impact of oral health and preventive dentistry.
Materials and methods. This was a cross-sectional descriptive-analytical study. Questionnaires were administered before and after an educational lecture to school health care instructors in Hamadan, Iran. Data were analyzed using paired t-test.
Results. In this study, 31 school health care instructors took part. The percentage of instructors in poor knowledge level was 22.6% before the educational lecture (education), which decreased to 0 percent after the education (P < 0.05). The percentage of instructors with good knowledge level was 3.2%, which increased to 80.6% after the education (P < 0.05).
Conclusion. Close cooperation between universities and the Ministry of Health and Medical Education will lead to improvements in the level of knowledge and awareness of school health care instructors.